Macroeconomic effects of fiscal policy under an energy supply shock - Johan Gustafsson; Xiaofei Ma; Junior Maih; Mathias Vesterberg (Norges Bank, 2024)
We study the potential effects on the real economy and welfare of four fiscal policy responses to an energy supply shock: energy vouchers to all households, only to lowincome households, or to non-energy goods producers, and subsidies for investments in the energy sector. The analysis relies on a DSGE model that explicitly models the energy sector. Calibrating the model to Swedish data, our results show that the subsidy for the investment in energy sector is the most effective instrument to reduce the energy price in the short- to medium term. This policy is, however, welfare dominated by energy vouchers given to households as it immediately compensates low-income, non-saving households in the event of the shock. Giving the energy voucher to the non-energy firms prevents energy prices from falling as fast as they would without policy intervention. It is also the least desirable from a welfare perspective.
hdl:11250/3172098
Keywords: D58; E62; H53; 330; energy price; Energy price; investment subsidy; energy voucher